Novel aspects targeting platelets in atherosclerotic cardiovascular disease: a translational perspective - Huseynov, Aydin; Reinhardt, Julius; Chandra, Leonard; Dürschmied, Daniel; Langer, Harald (International journal of molecular sciences, 2023)
Platelets are important cellular targets in cardiovascular disease. Based on insights from basic science, translational approaches and clinical studies, a distinguished anti-platelet drug treatment regimen for cardiovascular patients could be established. Furthermore, platelets are increasingly considered as cells mediating effects “beyond thrombosis”, including vascular inflammation, tissue remodeling and healing of vascular and tissue lesions. This review has its focus on the functions and interactions of platelets with potential translational and clinical relevance. The role of platelets for the development of atherosclerosis and therapeutic modalities for primary and secondary prevention of atherosclerotic disease are addressed. Furthermore, novel therapeutic options for inhibiting platelet function and the use of platelets in regenerative medicine are considered.